(untitled) (Agroindustria, Sociedad y Ambiente, 2023)
This study was conducted in the parish of San Isidro, located in the Macas canton, province of Morona Santiago, with the objective of analyzing the horchata produced by hand from the use of native plants of the Ecuadorian Amazon, to supplement the nutrition and health of the inhabitants of the region and generate added value for small farmers. The purpose of the study was to elaborate an Amazonian horchata and compare its physical, chemical and sensory characteristics with an industrialized horchata. For this purpose, the plants of interest were collected and a process of washing, drying, grinding and respective weighing was carried out. A factorial arrangement A (composition of medicinal plants) x B (coffee pulp) was used as experimental design, each one with 3 observations and infusions were made with each treatment to carry out a tasting test, in which 30 people from the area participated, where they were given to taste the Amazonian and the industrialized horchata, so that through a survey they could choose which one was their favorite. As a result, 12 tasters preferred treatment C3P1, which corresponds to (Jamaica, Hierba buena, Menta, Ishpingo, Hierba Luisa, Guayusa, Escancel) + coffee pulp, over the rest of the formulations and the control, indicating that its aroma, color and flavor were more attractive. In addition, the physicochemical comparison determined that the Amazonian horchata, unlike the traditional horchata, had a higher number of polyphenols with 5404 mg EAG kg-1, antioxidants with 48551 mg EAA kg-1, 39 ° Brix, an acidity of 0.6% and a pH of 4.20.